Exploring alternative paramedic roles: a multinational mixed-methods survey - Fintan Feerick; Eoin Coughlan; Shane Knox; Adrian Murphy; Ivan Grady; Conor Deasy (BMC Medical Education)
Abstract Background While paramedicine is an evolving profession globally, there remain many disparities around titles and roles within the various jurisdictions that may not be fully captured in the literature. Aim The aim of this study is to gain a multi-national perspective on the current and future roles within paramedicine, highlighting the challenges and opportunities that shape the profession’s ongoing evolution. Methods A mixed-methods approach was adopted for this survey, incorporating both quantitative and qualitative data. A survey link was distributed internationally to paramedicine professionals via email, journals, and social media. Quantitative data were analysed using Microsoft Excel’s statistical functions, with results presented as frequencies, percentages, and numerical summaries. Qualitative data were analysed using narrative synthesis and integrated with quantitative findings to provide a comprehensive overview. Results The study gathered responses from 158 participants representing 59 organisations across 16 countries. Ireland had the highest number of respondents (n = 56) followed by Australia (n = 41) and England (n = 21). Participants outlined current paramedic roles (n = 54) and future roles planned within their respective organisations (n = 39). Participants described aspirational, non-traditional roles that they felt paramedics may adopt into the future (n = 86). Respondents practitioner titles varied across a range of clinical, managerial, and academic specialties, with examples provided (n = 33). Respondents provided various descriptions of the clinical levels of practitioners available within their organisations (n = 41).Various ambulance care models were identified with various combinations (n = 24). Paramedic medical oversight was predominantly provided by a physician (n = 56) although (n = 22) other examples were described. Regulation of paramedic practice provided descriptions of various regulatory bodies (n = 8) with examples of paramedic models of regulation described (n = 9). Respondents described various patient safety framework models implemented within their respective organisations (n = 10). Conclusion The findings from this study highlight that paramedicine is rapidly evolving in response to varying local healthcare needs and sector-specific challenges. Rather than striving for a uniform standard of practice, the results suggest that paramedicine should be viewed as a flexible and adaptive domain, capable of specialising across diverse clinical, managerial, and academic settings. The diverse titles, roles, and models described by participants reflect the growing complexity of the profession. Furthermore, the study indicates that paramedic practice is often shaped by local contexts, such as organisational needs and healthcare gaps, which create innovative opportunities for expanding the scope of the profession. By embracing this variability and focusing on the development of versatile healthcare practitioners who can adapt to societal needs, paramedicine can continue to evolve effectively within well-governed healthcare systems.